Quantum dots and their applications
By forming a ligand layer of specific compounds on the surface of quantum dots, the problem of surface damage and reduced luminescence efficiency when quantum dots are dispersed in multiple solvents is solved, and the oxidation stability and reliability are improved, and in inkjet mode is achieved. It exhibits excellent dispersion and viscosity stability.
Patent Information
- Application Number
- CN202110185346.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-05
- Filing Date
- 2021-02-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-02-10
AI Technical Summary
When existing quantum dots are dispersed in various solvents or formed on the surface of specific functional groups, surface damage is easily caused, thereby reducing luminescence efficiency, and insufficient dispersion and viscosity stability, making it difficult to adapt to inkjet methods.
The compound represented by specific chemical formula 1 is formed as a ligand layer on the surface of the quantum dot, and the surface of the quantum dot is protected by the ligand layer, which improves oxidation stability and reliability, and is used in a photoconversion curable composition to improve dispersion and viscosity stability.
The oxidation stability and reliability of quantum dots are improved, which prevents the reduction of quantum efficiency, and exhibits excellent dispersion and viscosity stability in inkjet. It is suitable for a variety of applications, including quantum dot films and light emitting diodes. and image display device.
Smart Images

Figure BDA0002942850670000021 
Figure BDA0002942850670000033 
Figure BDA0002942850670000051
Abstract
Description
Technical Field
[0001] The present invention relates to quantum dots, a quantum dot dispersion containing the quantum dots, a photoconversion curable composition, a quantum dot light-emitting diode, a quantum dot film, a cured film formed using the photoconversion curable composition, and an image display device containing the cured film. Background Art
[0002] Quantum dots have high luminescence and a narrow luminescence spectrum. The luminescence wavelength can be adjusted by a single excitation wavelength, and they have stable intrinsic properties with respect to light. Therefore, to date, a lot of research has been conducted to use quantum dots in important application fields such as biological imaging or energy conversion, and lighting (LED).
[0003] Such quantum dots are very sensitive to the surface state. The surface will be oxidized by the dispersed solvent or the surrounding environment, resulting in a sharp drop in luminous efficiency. In order to achieve various applications of quantum dots, in addition to the organic solvent in which they are initially dispersed, they need to be dispersed in a variety of solvents or form specific functional groups on the surface. Due to this process, the surface of the quantum dots is damaged, resulting in a drop in luminous efficiency.
[0004] In order to overcome such problems, a large number of attempts have been made, and various methods have been proposed. One of them is the functional group replacement (ligand exchange) method of replacing the organic substance existing on the surface of the quantum dot with a molecule having a desired functional group. This method is a method of replacing the organic molecules existing on the surface of the quantum dot with the appropriate organic molecules to be applied, but since it will directly affect the surface of the quantum dot, it has the disadvantage of causing fatal problems to the luminous efficiency.
[0005] Korean Publication Patent No. 10-2018-0002716 and Korean Registration Patent No. 10-1628065 disclose quantum dots including ligands configured on the surface, but the actual situation is that the following problems cannot be solved: the dispersibility is reduced due to low compatibility, the stability and reliability are insufficient, the light resistance decreases over time, and the viscosity stability is insufficient and is not suitable for inkjet method, etc.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Korean Patent Publication No. 10-2018-0002716
[0009] Patent Document 2: Korean Registered Patent No. 10-1628065 Summary of the invention
[0010] Issues to be solved
[0011] An object of the present invention is to provide quantum dots having excellent optical properties, oxidation stability, and reliability.
[0012] Another object of the present invention is to provide a quantum dot dispersion having excellent dispersibility and viscosity stability.
[0013] Another object of the present invention is to provide a photoconversion curable composition which is excellent in photoconversion efficiency, coating film hardness, and adhesion and is suitable for an inkjet method.
[0014] In addition, an object of the present invention is to provide a quantum dot film and a quantum dot light-emitting diode (QLED) including the above-mentioned quantum dots.
[0015] Another object of the present invention is to provide a cured film formed using the above-mentioned photoconversion curable composition and an image display device including the above-mentioned cured film.
[0016] Solution to the problem
[0017] The present invention provides a quantum dot having a ligand layer on the surface.
[0018] The ligand layer includes a compound represented by the following Chemical Formula 1.
[0019] [Chemical formula 1]
[0020]
[0021] (In the above chemical formula 1,
[0022] A is a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, an aromatic hydrocarbon group having 6 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an alkynyl group having 2 to 30 carbon atoms, an alkyl ester group having 2 to 30 carbon atoms, a heteroaromatic hydrocarbon group having 4 to 30 carbon atoms, a thioether group, a thioester group having 1 to 30 carbon atoms, a silyl group, or a silyl ester group having 1 to 30 carbon atoms,
[0023] R1 and R2 are each independently directly bonded, a linear or branched alkylene group having 1 to 30 carbon atoms, -OR 11 -、-OC(=O)R 12 -、-(OCH2CH2) m -or-(OCH2CH2CH2) l -,
[0024] L1 and L2 are each independently a direct bond, an oxygen atom, a sulfur atom or -NH-,
[0025] D is an oxygen atom, a sulfur atom or =NH,
[0026] X is a thiol group, a carboxyl group, an amine group, a phosphate group, an imidazole group or a tetrazolyl group,
[0027] R 11 is a linear or branched alkylene group having 1 to 30 carbon atoms,
[0028] R 12 is a straight-chain or branched alkylene group having 4 to 30 carbon atoms,
[0029] m and l are each independently an integer of 1-150.
[0030] In the case where A is a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, or an aromatic hydrocarbon group having 6 to 30 carbon atoms, the above The resulting structure will not be )
[0031] In addition, the present invention provides a quantum dot dispersion liquid, a quantum dot light-emitting diode, a quantum dot film, and a light conversion curable composition containing the quantum dots.
[0032] Furthermore, the present invention provides a cured film formed using the above-mentioned photoconversion curable composition and an image display device including the above-mentioned cured film.
[0033] Effects of the Invention
[0034] The quantum dot of the present invention includes a compound represented by a specific chemical formula structure as a ligand layer, so that the surface of the quantum dot is protected and excellent in oxidation stability and reliability, and a decrease in quantum efficiency is prevented and excellent in optical characteristics.
[0035] Furthermore, the quantum dot ink composition and the photoconversion curable composition containing the quantum dots have high dispersibility and viscosity stability and are suitable even for a continuous process based on an inkjet method, and the coating film produced thereby exhibits excellent hardness and adhesion.
[0036] Therefore, the above-mentioned quantum dots and the light-conversion curable compositions containing the same provide the effect of improving optical properties such as brightness, reliability and process characteristics, and can be effectively used in a variety of applications such as quantum dot films, quantum dot light-emitting diodes, color filters, light-conversion laminated substrates, thereby providing high-quality image display devices. DETAILED DESCRIPTION
[0037] The present invention provides a quantum dot having a ligand layer on the surface, wherein the ligand layer comprises a compound represented by the following Chemical Formula 1.
[0038] [Chemical formula 1]
[0039]
[0040] (In the above chemical formula 1,
[0041] A is a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, an aromatic hydrocarbon group having 6 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an alkynyl group having 2 to 30 carbon atoms, an alkyl ester group having 2 to 30 carbon atoms, a heteroaromatic hydrocarbon group having 4 to 30 carbon atoms, a thioether group, a thioester group having 1 to 30 carbon atoms, a silyl group, or a silyl ester group having 1 to 30 carbon atoms,
[0042] R1 and R2 are each independently directly bonded, a linear or branched alkylene group having 1 to 30 carbon atoms, -OR 11 -、-OC(=O)R 12 -、-(OCH2CH2) m -or-(OCH2CH2CH2) l -,
[0043] L1 and L2 are each independently a direct bond, an oxygen atom, a sulfur atom or -NH-,
[0044] D is an oxygen atom, a sulfur atom or =NH,
[0045] X is a thiol group, a carboxyl group, an amine group, a phosphate group, an imidazole group or a tetrazolyl group,
[0046] R 11 is a linear or branched alkylene group having 1 to 30 carbon atoms,
[0047] R 12 is a straight-chain or branched alkylene group having 4 to 30 carbon atoms,
[0048] m and l are each independently an integer of 1-150.
[0049] In the case where A is a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, or an aromatic hydrocarbon group having 6 to 30 carbon atoms, the above The resulting structure will not be )
[0050] The quantum dot of the present invention is characterized in that it contains the compound represented by the above Chemical Formula 1 as a ligand layer, thereby preventing the quantum efficiency from being reduced due to oxidation of the quantum dot surface, and exhibiting excellent reliability and optical characteristics.
[0051] In addition, the present invention provides a quantum dot dispersion liquid comprising the above-mentioned quantum dots, a monomer, and one or more of a solvent.
[0052] Furthermore, the present invention provides a photoconversion curable composition comprising the quantum dot dispersion liquid.
[0053] In addition, the present invention provides a light-emitting diode (Quantum Dot Light-Emitting Diode, QLED) and a quantum dot film comprising the above-mentioned quantum dots.
[0054] Furthermore, the present invention provides a cured film formed using the above-mentioned photoconversion curable composition and an image display device including the above-mentioned cured film.
[0055] Hereinafter, the configuration of the present invention will be described in detail.
[0056] <Quantum dot>
[0057] In the present invention, quantum dots can emit light by themselves through a light source, and are used to emit light in the visible and infrared regions. Quantum dots are substances with a crystalline structure of several nanometers in size, and can be composed of hundreds to thousands of atoms. Atoms form molecules, and molecules form a collection of small molecules called molecular clusters to form nanoparticles. Usually, such nanoparticles are called quantum dots, especially when they have semiconductor properties. The quantum dots of the present invention are not particularly limited as long as they meet such a concept. When an object is as small as a nanometer or less, it will show a phenomenon that the band gap of the object becomes larger, which is the quantum confinement effect. If the quantum dot obtains energy from the outside and reaches an excited state, it will spontaneously release energy corresponding to the band gap and emit light by itself.
[0058] The quantum dot of the present invention is characterized in that it has a ligand layer on the surface, and the ligand layer contains a compound represented by the following chemical formula 1. This can protect the surface of the quantum dot, improve oxidation stability, prevent a decrease in quantum efficiency, and improve reliability.
[0059] [Chemical formula 1]
[0060]
[0061] In the above chemical formula 1, A can be a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, an aromatic hydrocarbon group having 6 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an alkynyl group having 2 to 30 carbon atoms, an alkyl ester group having 2 to 30 carbon atoms, a heteroaromatic hydrocarbon group having 4 to 30 carbon atoms, a thioether group, a thioester group having 1 to 30 carbon atoms, a silyl group, or a silyl ester group having 1 to 30 carbon atoms.
[0062] In the above chemical formula 1, R1 and R2 can each independently be a direct bond, a linear or branched alkylene group having 1 to 30 carbon atoms, -OR 11 -or-OC(=O)R 12 -、-(OCH2CH2) m -or-(OCH2CH2CH2) l -. The above R 11 It may be a linear or branched alkylene group having 1 to 30 carbon atoms, and preferably a linear or branched alkylene group having 1 to 20 carbon atoms. 12 The alkylene group may be a linear or branched alkylene group having 4 to 30 carbon atoms, and preferably a linear or branched alkylene group having 4 to 20 carbon atoms.
[0063] Furthermore, the above m and l may each independently be an integer of 1 to 150, and preferably an integer of 1 to 100.
[0064] In addition, in the above Chemical Formula 1, L1 and L2 may each independently be a direct bond, an oxygen atom, a sulfur atom or -NH-.
[0065] In addition, in the above Chemical Formula 1, D may be an oxygen atom, a sulfur atom or =NH.
[0066] In addition, in the above Chemical Formula 1, X may be a thiol group, a carboxyl group, an amine group, a phosphate group, an imidazole group or a tetrazolyl group, and preferably may be a thiol group, a carboxyl group, an amine group or a phosphate group.
[0067] In the above chemical formula 1, when A is a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, or an aromatic hydrocarbon group having 6 to 30 carbon atoms, The resulting structure will not be If A is a linear or branched alkyl group having 1 to 30 carbon atoms, a cycloalkyl group having 1 to 30 carbon atoms, or an aromatic hydrocarbon group having 6 to 30 carbon atoms, and the above The structure formed Correspondingly, there is a problem of reduced hardness of the coating film.
[0068] In one embodiment of the present invention, the compound represented by the above Chemical Formula 1 may be a compound represented by any one of the following Chemical Formulas 1-1 to 1-51.
[0069] [Chemical formula 1-1]
[0070]
[0071] [Chemical formula 1-2]
[0072]
[0073] [Chemical formula 1-3]
[0074]
[0075] [Chemical formula 1-4]
[0076]
[0077] [Chemical formula 1-5]
[0078]
[0079] [Chemical formula 1-6]
[0080]
[0081] [Chemical formula 1-7]
[0082]
[0083] [Chemical formula 1-8]
[0084]
[0085] [Chemical formula 1-9]
[0086]
[0087] [Chemical formula 1-10]
[0088]
[0089] [Chemical formula 1-11]
[0090]
[0091] [Chemical formula 1-12]
[0092]
[0093] [Chemical formula 1-13]
[0094]
[0095] In the above chemical formulae 1-10 to 1-13, n may be an integer of 1 to 150, and preferably an integer of 1 to 100.
[0096] [Chemical formula 1-14]
[0097]
[0098] [Chemical formula 1-15]
[0099]
[0100] [Chemical formula 1-16]
[0101]
[0102] [Chemical formula 1-17]
[0103]
[0104] [Chemical formula 1-18]
[0105]
[0106] [Chemical formula 1-19]
[0107]
[0108] [Chemical formula 1-20]
[0109]
[0110] [Chemical formula 1-21]
[0111]
[0112] [Chemical formula 1-22]
[0113]
[0114] [Chemical formula 1-23]
[0115]
[0116] [Chemical formula 1-24]
[0117]
[0118] [Chemical formula 1-25]
[0119]
[0120] [Chemical formula 1-26]
[0121]
[0122] [Chemical formula 1-27]
[0123]
[0124] [Chemical formula 1-28]
[0125]
[0126] [Chemical formula 1-29]
[0127]
[0128] [Chemical formula 1-30]
[0129]
[0130] [Chemical formula 1-31]
[0131]
[0132] [Chemical formula 1-32]
[0133]
[0134] [Chemical formula 1-33]
[0135]
[0136] [Chemical formula 1-34]
[0137]
[0138] [Chemical formula 1-35]
[0139]
[0140] [Chemical formula 1-36]
[0141]
[0142] [Chemical formula 1-37]
[0143]
[0144] [Chemical formula 1-38]
[0145]
[0146] [Chemical formula 1-39]
[0147]
[0148] [Chemical formula 1-40]
[0149]
[0150] [Chemical formula 1-41]
[0151]
[0152] [Chemical formula 1-42]
[0153]
[0154] [Chemical formula 1-43]
[0155]
[0156] [Chemical formula 1-44]
[0157]
[0158] [Chemical formula 1-45]
[0159]
[0160] [Chemical formula 1-46]
[0161]
[0162] [Chemical formula 1-47]
[0163]
[0164] [Chemical formula 1-48]
[0165]
[0166] [Chemical formula 1-49]
[0167]
[0168] [Chemical formula 1-50]
[0169]
[0170] [Chemical formula 1-51]
[0171]
[0172] The compound represented by the above chemical formula 1 of the present invention is coordinated and bound to the surface of the quantum dot as an organic ligand and can play a role in stabilizing the quantum dot. In general, the quantum dots usually manufactured have a ligand layer on the surface. Just after manufacturing, the ligand layer can be composed of oleic acid, lauric acid, 2-(2-methoxyethoxy)acetic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and succinic acid mono-[2-(2-methoxy-ethoxy)-ethyl] ester. In this case, compared with the quantum dots of the present invention comprising the compound represented by the above chemical formula 1 as a ligand layer, the surface protection effect may be reduced due to the non-binding defects on the surface of the quantum dots. In addition, for oleic acid, although it is easy to disperse in saturated hydrocarbon solvents such as n-hexane, chloroform, and aromatic solvents such as benzene, which are highly volatile compounds (VOC; volatile organic compounds), it has poor dispersibility in solvents such as PGMEA.
[0173] The quantum dots of the present invention include the compound represented by the above chemical formula 1 in the ligand layer, so that the surface of the quantum dots is protected. Therefore, compared with previous quantum dots, they can show excellent oxidation stability and have very excellent dispersibility in solvents such as PGMEA, which has the effect of improving optical properties.
[0174] In some embodiments, the quantum dots of the present invention include the compound represented by the above chemical formula 1 in the ligand layer, and may further include oleic acid, lauric acid, 2-(2-methoxyethoxy)acetic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and succinic acid mono-[2-(2-methoxy-ethoxy)-ethyl] ester, etc.
[0175] The quantum dots are not particularly limited as long as they are quantum dot particles that can emit light through stimulation by light or electricity. For example, they can be selected from the group consisting of II-VI semiconductor compounds; III-V semiconductor compounds; IV-VI semiconductor compounds; IV elements or compounds containing them; and combinations thereof, and they can be used alone or in combination of two or more.
[0176] For example, the above-mentioned II-VI semiconductor compound can be selected from the group consisting of the following compounds: a binary compound selected from the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe and a mixture thereof; a binary compound selected from the group consisting of CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe , CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe and a mixture thereof; and a four-element compound selected from the group consisting of CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe and a mixture thereof, but not limited to this.
[0177] The above-mentioned III-V Group semiconductor compounds can be selected from the group consisting of the following compounds: a two-element compound selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb and a mixture thereof; a three-element compound selected from the group consisting of GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP and a mixture thereof; and a four-element compound selected from the group consisting of GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb and a mixture thereof, but is not limited thereto.
[0178] The above-mentioned Group IV-VI semiconductor compounds can be selected from the group consisting of the following compounds: two-element compounds selected from the group consisting of SnS, SnSe, SnTe, PbS, PbSe, PbTe and mixtures thereof; three-element compounds selected from the group consisting of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe and mixtures thereof; and four-element compounds selected from the group consisting of SnPbSSe, SnPbSeTe, SnPbSTe and mixtures thereof, but are not limited to these.
[0179] Although not limited thereto, the Group IV element or a compound containing the same may be selected from the group consisting of an element selected from the group consisting of Si, Ge and a mixture thereof; and a binary compound selected from the group consisting of SiC, SiGe and a mixture thereof.
[0180] Quantum dots can be a homogeneous single structure; a dual structure such as a core-shell structure and a gradient structure; or a mixed structure thereof. In the present invention, the type of quantum dots is not particularly limited as long as they can emit light through stimulation by light.
[0181] According to one embodiment, the quantum dots have a core-shell structure, and the core may include one or more selected from the group consisting of InP, InZnP, InGaP, CdSe, CdS, CdTe, ZnS, ZnSe, ZnTe, CdSeTe, CdZnS, CdSeS, PbSe, PbS, PbTe, AgInZnS, AgInGaS, HgS, HgSe, HgTe, GaN, GaP, GaAs, InGaN, InAs and ZnO, but is not limited thereto.
[0182] In addition, in the above-mentioned core-shell structure, the above-mentioned shell may include one or more selected from the group consisting of ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, InP, InS, GaP, GaN, GaO, GaS, InZnP, InGaP, InGaN, InZnSCdSe, PbS, TiO, SrSe and HgSe, but is not limited to this.
[0183] According to one embodiment, the core-shell structured quantum dots may include one or more selected from the group consisting of AgInGaS / GaS, InP / ZnS, InP / ZnSe, InP / GaP / ZnS, InP / ZnSe / ZnS, InP / ZnSeTe / ZnS and InP / MnSe / ZnS, but are not limited thereto.
[0184] Generally speaking, quantum dots can be manufactured by a wet chemical process, a metal organic chemical vapor deposition (MOCVD) process, or a molecular beam epitaxy (MBE) process.
[0185] The quantum dots of the present invention can be synthesized by wet chemical processes.
[0186] The above-mentioned wet chemical process is a method of adding precursor substances to an organic solvent to grow particles. When the crystals grow, the organic solvent naturally coordinates to the surface of the quantum dot crystals and plays the role of a dispersant, thereby controlling the growth of the crystals. Therefore, compared with vapor phase evaporation methods such as organic metal chemical evaporation or molecular beam epitaxy, the size growth of quantum dot particles can be controlled through an easier and cheaper process.
[0187] When quantum dots are produced by a wet chemical process, an organic ligand is used to prevent aggregation of quantum dots and control the particle size of quantum dots to a nanometer level. As such an organic ligand, oleic acid is generally used.
[0188] In one embodiment of the present invention, the oleic acid used in the manufacturing process of the quantum dots is replaced by the compound represented by the chemical formula 1 through a ligand exchange method.
[0189] The ligand exchange can be carried out as follows: the organic ligand to be exchanged, i.e., the compound represented by Chemical Formula 1, is added to a dispersion containing quantum dots having the original organic ligand, i.e., oleic acid, and then stirred at room temperature to 200° C. for 30 minutes to 3 hours to obtain quantum dots bound with the compound represented by Chemical Formula 1. If necessary, a process of separating and purifying the quantum dots bound with the compound represented by the above Chemical Formula 1 can be further carried out.
[0190] As described above, the quantum dots according to one embodiment of the present invention have the advantage that they can be produced by an organic ligand exchange method that involves a simple stirring process at room temperature and can be mass-produced.
[0191] Furthermore, the quantum dots according to one embodiment of the present invention can maintain a quantum efficiency of about 90% or more compared to the initial quantum efficiency even after 15 days, and thus can be stably stored for a long period of time and can be commercialized for a variety of uses.
[0192] <Quantum Dot Dispersion>
[0193] A quantum dot dispersion according to an embodiment of the present invention is characterized in that it contains the quantum dots described above and contains one or more of a monomer and a solvent.
[0194] quantum dots
[0195] The content of the quantum dots may be 10 to 90% by weight, preferably 20 to 80% by weight, and more preferably 30 to 70% by weight, compared to the total weight of the quantum dot dispersion. When the content of the quantum dots is within the above range, the light-emitting efficiency is excellent, and the reliability of the light-conversion coating produced by the light-conversion curable composition is excellent. When the content of the quantum dots is within the above range, the dispersibility characteristics of the quantum dots are good, the coating or spraying characteristics are excellent, and the optical characteristics and reliability are excellent, so it is preferred.
[0196] monomer
[0197] The above monomers play a role in improving the dispersibility of quantum dots.
[0198] Examples of the monomer include monofunctional monomers, difunctional monomers, and other polyfunctional monomers, and difunctional or higher-functional monomers are preferably used.
[0199] The type of the monofunctional monomer is not particularly limited, and examples thereof include nonylphenyl carbitol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-ethylhexyl carbitol acrylate, and 2-hydroxyethyl acrylate.
[0200] The type of the bifunctional monomer is not particularly limited, and examples thereof include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, bis(acryloyloxyethyl) ether of bisphenol A, and 3-methylpentanediol di(meth)acrylate.
[0201] The type of the above-mentioned multifunctional monomer is not particularly limited, and examples thereof include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, propoxylated dipentaerythritol hexa(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0202] When the quantum dot dispersion of the present invention contains the above-mentioned monomer, the content of the monomer may be 10 to 90% by weight, preferably 20 to 80% by weight, and more preferably 30 to 70% by weight relative to the total weight of the quantum dot dispersion. When the content of the above-mentioned monomer is within the above-mentioned range, the dispersibility characteristics of the quantum dots are good, the coating or spraying characteristics are excellent, and the optical characteristics and reliability are excellent, so it is preferred.
[0203] In the present invention, the description of the above-mentioned monomers is also applicable to monomers contained in the photoconversion curable composition and quantum dot ink composition described later.
[0204] Solvents
[0205] As long as the solvent is effective in dissolving other components contained in the quantum dot dispersion, any solvent commonly used in the art can be used without particular limitation. As specific examples of the solvent, one or more can be selected from ethers, acetates, aromatic hydrocarbons, ketones, alcohols, esters, and amides, but the invention is not limited thereto.
[0206] The ether solvents specifically include ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether;
[0207] Propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether and propylene glycol monobutyl ether;
[0208] Diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether; etc.
[0209] Specific examples of the acetate solvents include alkylene glycol alkyl ether acetates such as methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate;
[0210] Alkoxyalkyl acetates such as methoxybutyl acetate, methoxypentyl acetate, and n-pentyl acetate; etc.
[0211] Specific examples of the aromatic hydrocarbon solvent include benzene, toluene, xylene, and mesitylene.
[0212] Specific examples of the ketone solvent include methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0213] Specific examples of the alcohol solvent include ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol, glycerol, and the like.
[0214] Specific examples of the ester solvents include cyclic esters such as γ-butyrolactone, ethyl 3-ethoxypropionate, methyl 3-methoxypropionate, and ethyl 3-ethoxypropionate.
[0215] Specific examples of the amide solvents include N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0216] These solvents may be used alone or in combination of two or more.
[0217] When the quantum dot dispersion of the present invention includes the above-mentioned solvent, the content of the solvent may be 10 to 90% by weight, preferably 20 to 80% by weight, and more preferably 30 to 70% by weight relative to the total weight of the quantum dot dispersion. When the content of the above-mentioned solvent is within the above-mentioned range, the dispersibility characteristics of the quantum dots are good, the coating or spraying characteristics are excellent, and the optical characteristics and reliability are excellent, so it is preferred.
[0218] In the present invention, the description of the above-mentioned solvent is also applicable to the solvent contained in the photoconversion curable composition and the quantum dot ink composition described later.
[0219] <Photoconversion curable composition>
[0220] A photoconversion curable composition according to one embodiment of the present invention is characterized by including the above-mentioned quantum dots or quantum dot dispersion.
[0221] The above-mentioned light conversion curable composition can be a light conversion ink composition or a light conversion resin composition. The light conversion curable composition of one embodiment of the present invention can be a solvent-free type that does not contain a solvent in terms of continuous processability. The above-mentioned quantum dot ink composition has high dispersibility and viscosity stability, and can therefore be suitably used in a continuous process based on an inkjet method.
[0222] In addition, the photoconversion curable composition may further include one or more scattering particles, an alkali-soluble resin, a photopolymerizable compound, a photopolymerization initiator, a solvent, etc., as required. The description of the solvent is the same as that of the quantum dot dispersion.
[0223] The method for producing the photoconversion curable composition of the present invention is not particularly limited, and a method known in the technical field can be used.
[0224] Scattering particles
[0225] The scattering particles may be made of common inorganic materials, and preferably may include a metal oxide having an average particle size of 30 to 1000 nm.
[0226] The above-mentioned metal oxide can be an oxide of a metal selected from the group consisting of Li, Be, B, Na, Mg, Al, Si, K, Ca, Sc, V, Cr, Mn, Fe, Ni, Cu, Zn, Ga, Ge, Rb, Sr, Y, Mo, Cs, Ba, La, Hf, W, Tl, Pb, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Ti, Sb, Sn, Zr, Nb, Ce, Ta, In and combinations thereof, but is not limited thereto.
[0227] Specifically, it can be one selected from the group consisting of Al2O3, SiO2, ZnO, ZrO2, BaTiO3, TiO2, Ta2O5, Ti3O5, ITO, IZO, ATO, ZnO-Al, Nb2O3, SnO, MgO and combinations thereof. If necessary, a material surface-treated with a compound having an unsaturated bond such as acrylate can also be used.
[0228] When the quantum dot light conversion composition of the present invention contains scattering particles, the scattering particles can increase the path of light spontaneously emitted from the quantum dots and improve the overall light efficiency of the color filter, which is preferred.
[0229] Preferably, the scattering particles may have an average particle size of 30 to 1000 nm, preferably 100 to 500 nm. At this time, if the particle size is too small, sufficient scattering effect of light released from the quantum dots cannot be expected. On the contrary, if it is too large, it may be deposited in the composition, or a uniform quality of the self-luminous layer surface may not be obtained. Therefore, it is appropriately adjusted within the above range.
[0230] Alkali soluble resin
[0231] The alkali-soluble resin may be one or more selected from the group consisting of acrylic alkali-soluble resins and Cardo alkali-soluble resins.
[0232] The acrylic alkali-soluble resin or Cardo alkali-soluble resin has reactivity with the action of light or heat, and plays a role in improving the dispersibility of quantum dots. The acrylic alkali-soluble resin or Cardo alkali-soluble resin contained in the photoconversion curable composition of the present invention is not particularly limited as long as it can act as a binder resin for quantum dots and can be used as a support for the photoconversion coating.
[0233] Photopolymerizable compounds
[0234] Examples of the photopolymerizable compound include monofunctional monomers, difunctional monomers, and other polyfunctional monomers, and preferably difunctional or higher-functional monomers are used.
[0235] The type of the monofunctional monomer is not particularly limited, and examples thereof include nonylphenyl carbitol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-ethylhexyl carbitol acrylate, and 2-hydroxyethyl acrylate.
[0236] The type of the bifunctional monomer is not particularly limited, and examples thereof include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, bis(acryloyloxyethyl) ether of bisphenol A, and 3-methylpentanediol di(meth)acrylate.
[0237] The type of the above-mentioned multifunctional monomer is not particularly limited, and examples thereof include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, propoxylated dipentaerythritol hexa(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0238] Photopolymerization initiator
[0239] The above-mentioned photopolymerization initiator is a compound used to initiate the polymerization of the photopolymerizable compound described above. There is no particular limitation in the present invention, but from the viewpoints of polymerization characteristics, initiation efficiency, absorption wavelength, availability, price, etc., it is preferred to use one or more compounds selected from the group consisting of acetophenone compounds, benzophenone compounds, triazine compounds, biimidazole compounds, oxime compounds, acylphosphine compounds and thioxanthone compounds.
[0240] The light conversion curable composition produced in this way can be preferably used to produce a cured film such as a color filter or a light conversion laminated substrate, and an image display device including the same.
[0241] <Quantum Dot Light Emitting Diodes>
[0242] A quantum dot light-emitting diode (QLED) according to an embodiment of the present invention may include the aforementioned quantum dots.
[0243] The quantum dot light-emitting diode is an electroluminescence (EL) device in which quantum dots are electrically excited to emit light.
[0244] In the case of the quantum dot light-emitting diode, the electrons and holes injected from the electrodes on both sides form excitons in the quantum dot light-emitting layer, and light is emitted through the radiative recombination of the excitons. Since the working principle is the same as that of the organic light-emitting diode (OLED), it can be constructed by directly using the multi-layer element structure of the electron / hole injection layer and the transport layer of the conventional OLED, and only replacing the organic light-emitting element with quantum dots in the light-emitting layer.
[0245] The method for producing the quantum dot light-emitting diode of the present invention is not particularly limited, and a method known in the technical field can be used.
[0246] In one embodiment, the method for manufacturing a quantum dot light emitting diode may be manufactured by sequentially stacking an anode, a cathode, an electron injection / transport layer, a light emitting layer, a hole transport layer, and a hole injection layer.
[0247] In another embodiment, the method for manufacturing a quantum dot light-emitting diode can also be manufactured by sequentially stacking a cathode, an electron injection / transport layer, a light-emitting layer, a hole transport layer, a hole injection layer and an anode. In yet another embodiment, the method for manufacturing a quantum dot light-emitting diode can also be manufactured by sequentially stacking an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, an electron injection / transport layer and a cathode.
[0248] In this case, the light-emitting layer may include the quantum dots.
[0249] <Quantum dot film>
[0250] The quantum dot film according to an embodiment of the present invention may include the above-mentioned quantum dots.
[0251] The quantum dot film includes a quantum dot dispersion layer including a polymer resin and the quantum dots dispersed in the polymer resin.
[0252] As the above-mentioned polymer resin, for example, epoxy resin, epoxy acrylate, lauryl acrylate, norbornene, polyethylene, polystyrene, ethylene-styrene copolymer, acrylate containing bisphenol A and bisphenol A derivatives, acrylate containing fluorene derivatives, isobornyl acrylate, polyphenylalkylsiloxane, polydiphenylsiloxane, polydialkylsiloxane, silsesquioxane, fluorinated silicone, and vinyl and hydride substituted silicone, etc. can be used. These polymer resins can be used alone or in combination of two or more.
[0253] The quantum dot film may further include a barrier layer on at least one surface of the quantum dot dispersion layer.
[0254] The barrier layer may have a thickness of 0.001 cm 3 / ㎡·day·bar(cm 3 The polyurethane foam has an oxygen permeability of less than 0.001 g / ㎡·day (g / ㎡·day) and a water permeability of less than 0.001 g / ㎡·day, and may include, for example, polyester, polycarbonate, polyolefin, cyclic olefin polymer or polyimide.
[0255] The thickness of the quantum dot dispersion layer may be 10 μm to 100 μm, and the thickness of the barrier layer may be 50 μm to 70 μm.
[0256] The method for producing the quantum dot film of the present invention is not particularly limited, and a method known in the technical field can be used.
[0257] In one embodiment, the method for manufacturing a quantum dot film may include:
[0258] a) preparing a lower transparent substrate;
[0259] b) coating the quantum dot dispersion on the lower transparent substrate to form a quantum dot film; and
[0260] c) A step of laminating an upper transparent substrate on the quantum dot thin film to produce a quantum dot film.
[0261] <Cured Film>
[0262] The present invention provides a cured film formed using the above-mentioned photoconversion curable composition. The above-mentioned cured film may be a color filter or a photoconversion laminate substrate.
[0263] Color Filters
[0264] The pattern forming method for forming the color filter of the present invention can be a method known in the art.
[0265] In one embodiment, the pattern forming method may include:
[0266] a) applying a quantum dot ink composition or a light-converting curable composition to a substrate;
[0267] b) a pre-baking step to dry the solvent;
[0268] c) irradiating the obtained film with active light through a photomask to cure the exposed portion;
[0269] d) performing a developing step of dissolving the unexposed portion using an alkaline aqueous solution; and
[0270] e) performing drying and post-baking steps.
[0271] The substrate may be a glass substrate or a polymer substrate, but is not limited thereto. As the glass substrate, soda-lime glass, glass containing barium or strontium, lead glass, aluminum silicate glass, borosilicate glass, barium borosilicate glass or quartz may be particularly preferably used. In addition, as the polymer substrate, polycarbonate, acrylic, polyethylene terephthalate, polyether sulfide or polysulfone substrates may be cited.
[0272] In order to obtain a desired thickness, coating can be performed by a known wet coating method using a coating device such as a roll coater, a spin coater, a slot spin coater, a slot coater (sometimes also called a die coater), or an inkjet machine.
[0273] Pre-baking is performed by heating in an oven, a hot plate, etc. At this time, the heating temperature and heating time during pre-baking are appropriately selected according to the solvent used, and for example, the pre-baking can be performed at a temperature of 80 to 150° C. for 1 to 30 minutes.
[0274] The exposure after pre-baking is performed by using an exposure machine and exposing through a photomask so that only the portion corresponding to the pattern is exposed to light. At this time, the light used for irradiation may be, for example, visible light, ultraviolet light, X-rays, electron beams, etc.
[0275] The developing step of dissolving the unexposed part with an alkaline aqueous solution after exposure is performed for the purpose of removing the unremoved part of the photosensitive resin composition of the unexposed part, and the desired pattern is formed by the development. As a developer suitable for the development with the alkaline aqueous solution, for example, an aqueous solution of a carbonate of an alkali metal or an alkaline earth metal can be used. In particular, the alkaline aqueous solution containing 1 to 3% by weight of a carbonate such as sodium carbonate, potassium carbonate, lithium carbonate, etc. can be used at a temperature of 10 to 50°C, preferably 20 to 40°C, using a developing machine or an ultrasonic cleaning agent.
[0276] Post-baking is performed to improve the adhesion between the patterned film and the substrate, and can be achieved by, for example, heat treatment at 80 to 250° C. for 10 to 120 minutes. Post-baking can be performed using an oven, a hot plate, or the like, similar to pre-baking.
[0277] Light conversion laminate substrate
[0278] The light conversion laminate substrate of the present invention comprises a cured product of a light conversion curable composition. The light conversion laminate substrate comprises a light conversion curable composition that can be applied to a glass substrate, thereby enabling the use of a solvent that is not harmful to human health, thereby improving operator safety and product productivity.
[0279] The light conversion layered substrate may be silicon (Si), silicon oxide (SiOx) or a polymer substrate. The polymer substrate may be polyethersulfone (PES) or polycarbonate (PC).
[0280] The light conversion laminate substrate can be formed by applying the light conversion curable composition and performing thermal curing or photocuring.
[0281] <Image Display Device>
[0282] The image display device of the present invention comprises the above-mentioned cured film, i.e., a color filter or a light conversion laminated substrate. The above-mentioned image display device specifically includes a liquid crystal display (liquid crystal display device; LCD), an organic EL display (organic EL display device), a liquid crystal projector, a display device for a game console, a display device for a portable terminal such as a mobile phone, a display device for a digital camera, a display device for a car navigation system, and the like, and is particularly suitable for a color display device.
[0283] In addition to the color filter or light conversion stack substrate, the image display device may further include a structure known to those skilled in the art in the technical field of the present invention. That is, the present invention includes an image display device to which the color filter or light conversion stack substrate can be applied.
[0284] An image display device including the color filter of the present invention can have excellent characteristics in terms of color reproducibility, brightness, light resistance, reliability, and the like.
[0285] Hereinafter, the present invention will be described in more detail by way of examples. However, the following examples are provided to more specifically describe the present invention, and the scope of the present invention is not limited to the following examples.
[0286] <Example>
[0287] Synthesis Example 1: InP / ZnSe / ZnS Core-Shell Quantum Dot Synthesis
[0288] 0.4 mmol (0.058 g) of indium acetate, 0.6 mmol (0.15 g) of palmitic acid, and 20 mL of 1-octadecene were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was switched to nitrogen. After heating to 280°C, 0.2 mmol of tris(trimethylsilyl)phosphine (TMS3P) was quickly injected. and 1.0 mL of a mixed solution of trioctylphosphine, and react for 0.5 minutes.
[0289] Next, 2.4mmoL (0.448g) of zinc acetate, 4.8mmol of oleic acid and 20mL of trioctylamine were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was converted to nitrogen and the reactor was heated to 280°C. 2mL of the previously synthesized InP core solution was added, followed by 4.8mmol of selenium (Se / TOP) in trioctylphosphine, and the final mixture was reacted for 2 hours. Ethanol was added to the reaction solution that was rapidly cooled to room temperature, and centrifuged. The resulting precipitate was filtered under reduced pressure and then dried under reduced pressure to form an InP / ZnSe core-shell.
[0290] Next, 2.4mmol (0.448g) of zinc acetate, 4.8mmol of oleic acid and 20mL of trioctylamine were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was converted to nitrogen and the reactor was heated to 280°C. 2mL of the previously synthesized InP / ZnSe core-shell solution was added, followed by 4.8mmol of sulfur (S / TOP) in trioctylphosphine, and the final mixture was reacted for 2 hours. Ethanol was added to the reaction solution that was rapidly cooled to room temperature, and centrifuged. The resulting precipitate was filtered under reduced pressure, and then dried under reduced pressure to obtain quantum dots of InP / ZnSe / ZnS core-shell structure, which were then dispersed in chloroform. The solid content was adjusted to 10%. The maximum emission wavelength was 520nm.
[0291] Examples 1-1 to 1-51 and Comparative Examples 1-1 to 1-8: Preparation of Quantum Dots
[0292] Example 1-1: Ligand Substitution Reaction 1 (LE-1)
[0293] 5 mL of the quantum dot solution obtained in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to precipitate it. The supernatant was removed by centrifugation, and 3 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 1.0 g of 2-mercaptoethyl methyl glutarate (2-Mercaptoethyl methyl glutarate (Alfa Chemistry)) represented by the following chemical formula 1-1 was added, and the mixture was heated at 60°C under a nitrogen atmosphere and reacted for one hour.
[0294] [Chemical formula 1-1]
[0295]
[0296] Next, 25 mL of n-hexane was added to the reaction product to precipitate the quantum dots, and then centrifugation was performed to separate the precipitate to obtain a ligand-substituted quantum dot powder (LE-1). The maximum emission wavelength was 520 nm.
[0297] Example 1-2. Ligand Substitution Reaction 2 (LE-2)
[0298] The same procedure as in Example 1-1 was carried out except that allyl-mercaptooctanoate (ChemTik) represented by the following chemical formula 1-2 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0299] [Chemical formula 1-2]
[0300]
[0301] Example 1-3. Ligand Substitution Reaction 3 (LE-3)
[0302] The same procedure as in Example 1-1 was performed except that 4-oxo-4-(prop-2-yn-1-ylamino)butanoic acid (Combi-Blocks Inc.) represented by the following chemical formula 1-3 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0303] [Chemical formula 1-3]
[0304]
[0305] Example 1-4. Ligand Substitution Reaction 4 (LE-4)
[0306] The same procedure as in Example 1-1 was followed except that propionic acid, 3-(acetylthio)-, carboxymethyl ester (Angene Chemical Co., Ltd.) represented by the following chemical formula 1-4 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 520 nm.
[0307] [Chemical formula 1-4]
[0308]
[0309] Example 1-5. Ligand Substitution Reaction 5 (LE-5)
[0310] The same procedure as in Example 1-1 was followed except that succinic acid, mono[2-(trimethylsilyl)ethyl]ester (ChemTik) represented by the following chemical formula 1-5 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0311] [Chemical formula 1-5]
[0312]
[0313] Example 1-6. Ligand Substitution Reaction 6 (LE-6)
[0314] The same procedure as in Example 1-1 was followed except that 2-(3-trihydroxysilylpropylcarbamoylamino)acetic acid (ChemTik) represented by the following chemical formula 1-6 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0315] [Chemical formula 1-6]
[0316]
[0317] Example 1-7. Ligand Substitution Reaction 7 (LE-7)
[0318] The same procedure as in Example 1-1 was carried out except that 6-[(Cyclohexylcarbamoyl)amino]hexanoic acid (Ambeed) represented by the following chemical formula 1-7 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0319] [Chemical formula 1-7]
[0320]
[0321] Example 1-8. Ligand Substitution Reaction 8 (LE-8)
[0322] The same procedure as in Example 1-1 was carried out except that 6-(3-phenylureido)hexanoic acid (Angene Chemical Co., Ltd.) represented by the following chemical formula 1-8 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0323] [Chemical formula 1-8]
[0324]
[0325] Example 1-9. Ligand Substitution Reaction 9 (LE-9)
[0326] The same procedure as in Example 1-1 was performed except that 3-[((benzylthio)carbonothioyl)thio]propanoic acid (TCI) represented by the following chemical formula 1-9 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0327] [Chemical formula 1-9]
[0328]
[0329] Example 1-10. Ligand Substitution Reaction 10 (LE-10)
[0330] The same procedure as in Example 1-1 was carried out except that SH-PEG-Silane (SH-PEG-Silane, Biochempeg, MW600) represented by the following chemical formula 1-10 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 520 nm.
[0331] [Chemical formula 1-10]
[0332]
[0333] Example 1-11. Ligand Substitution Reaction 11 (LE-11)
[0334] The same procedure as in Example 1-1 was performed except that silane-PEG-NH2 (Silane-PEG-NH2, Biochempeg, MW1K) represented by the following chemical formula 1-11 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 520 nm.
[0335] [Chemical formula 1-11]
[0336]
[0337] Example 1-12. Ligand Substitution Reaction 12 (LE-12)
[0338] The same procedure as in Example 1-1 was performed except that monoethoxysilane-PEG-NH2 (Biochempeg, MW5K) represented by the following chemical formula 1-12 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0339] [Chemical formula 1-12]
[0340]
[0341] Example 1-13. Ligand Substitution Reaction 13 (LE-13)
[0342] The same procedure as in Example 1-1 was performed except that silane-PEG-NH2 (Silane-PEG-NH2, Nanosoft Polymers, MW1K) represented by the following chemical formula 1-13 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0343] [Chemical formula 1-13]
[0344]
[0345] Example 1-14. Ligand Substitution Reaction 14 (LE-14)
[0346] The same procedure as in Example 1-1 was carried out except that N-(benzyloxycarbonyl)aminomethylphosphonic acid (Chemspace) represented by the following chemical formula 1-14 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 523 nm.
[0347] [Chemical formula 1-14]
[0348]
[0349] Example 1-15. Ligand Substitution Reaction 15 (LE-15)
[0350] The same procedure as in Example 1-1 was followed except that N-Fmoc-1-aminomethylphosphonic acid (BOC Sciences) represented by the following chemical formula 1-15 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 523 nm.
[0351] [Chemical formula 1-15]
[0352]
[0353] Example 1-16. Ligand Substitution Reaction 16 (LE-16)
[0354] The same procedure as in Example 1-1 was carried out except that 2-(2'-acetoxypropanoyloxy)propanoic acid (Aurora Fine Chemicals) represented by the following Chemical Formula 1-16 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0355] [Chemical formula 1-16]
[0356]
[0357] Example 1-17. Ligand Substitution Reaction 17 (LE-17)
[0358] The same procedure as in Example 1-1 was carried out except that 5-methoxycarbonyl-4-oxopentanoic acid (ChemTik) represented by the following chemical formula 1-17 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0359] [Chemical formula 1-17]
[0360]
[0361] Example 1-18. Ligand Substitution Reaction 18 (LE-18)
[0362] The same method as in Example 1-1 was used except that 4-oxo-1,7-heptanedionic acid, monomethyl ester (self-synthesized; Synthetic Communications, 1983, vol. 13, #3, p. 243-254) represented by the following chemical formula 1-18 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 523 nm.
[0363] [Chemical formula 1-18]
[0364]
[0365] Example 1-19. Ligand Substitution Reaction 19 (LE-19)
[0366] The same procedure as in Example 1-1 was followed except that 2-(2-methoxy-2-oxoacetamido)acetic acid (Debye Scientific Co., Ltd.) represented by the following chemical formula 1-19 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0367] [Chemical formula 1-19]
[0368]
[0369] Example 1-20. Ligand Substitution Reaction 20 (LE-20)
[0370] The same procedure as in Example 1-1 was performed except that methoxyoxalyl-2-(4-imidazolyl)ethylamide (self-synthesized; Nucleosides, nucleotides and nucleic acids, 2005, vol. 24, #9, p. 1333-1343) represented by the following chemical formula 1-20 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0371] [Chemical formula 1-20]
[0372]
[0373] Example 1-21. Ligand Substitution Reaction 21 (LE-21)
[0374] The same procedure as in Example 1-1 was performed except that 8-methoxy-6-oxo-octanoic acid (synthesized by the method of Journal of the American Chemical Society, 1955, vol. 77, p. 2534) represented by the following chemical formula 1-21 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0375] [Chemical formula 1-21]
[0376]
[0377] Example 1-22. Ligand Substitution Reaction 22 (LE-22)
[0378] The same procedure as in Example 1-1 was followed except that 3-(2-methoxy-ethylcarbamoylsulfanyl)-propionic acid (Angene International Limited) represented by the following chemical formula 1-22 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0379] [Chemical formula 1-22]
[0380]
[0381] Example 1-23. Ligand Substitution Reaction 23 (LE-23)
[0382] The same procedure as in Example 1-1 was carried out except that (pentanimidoylamino)acetic acid (BOC Sciences) represented by the following chemical formula 1-23 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 523 nm.
[0383] [Chemical formula 1-23]
[0384]
[0385] Example 1-24. Ligand Substitution Reaction 24 (LE-24)
[0386] The same procedure as in Example 1-1 was performed except that methylcarbamimidoylmercapto-acetic acid (self-synthesized; Acta Chemica Scandinavica (1947), 1967, vol. 21, p. 843-848; CAS No. 16312-22-4) represented by the following chemical formula 1-24 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0387] [Chemical formula 1-24]
[0388]
[0389] Example 1-25. Ligand Substitution Reaction 25 (LE-25)
[0390] The same method as in Example 1-1 was used except that (N'-ethylguanidino)acetic acid (self-synthesized; Organic and Biomolecular Chemistry, 2012, vol. 10, #5, p. 978-987; CAS No. 16974-45-1) represented by the following chemical formula 1-25 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0391] [Chemical formula 1-25]
[0392]
[0393] Example 1-26. Ligand Substitution Reaction 26 (LE-26)
[0394] The same procedure as in Example 1-1 was performed except that 2-[2-(1(3)H-imidazol-4-yl)-ethyl]-1-methyl-isothiourea (Angene Chemical Co., Ltd.) represented by the following chemical formula 1-26 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0395] [Chemical formula 1-26]
[0396]
[0397] Example 1-27. Ligand Substitution Reaction 27 (LE-27)
[0398] The same procedure as in Example 1-1 was performed except that 2-(allyloxy)ethyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-27 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0399] [Chemical formula 1-27]
[0400]
[0401] Example 1-28. Ligand Substitution Reaction 28 (LE-28)
[0402] The same procedure as in Example 1-1 was performed except that 2-(2-(allyloxy)ethoxy)ethyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726)) represented by the following chemical formula 1-28 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0403] [Chemical formula 1-28]
[0404]
[0405] Example 1-29. Ligand Substitution Reaction 29 (LE-29)
[0406] The same procedure as in Example 1-1 was performed except that 2-(2-(2-(allyloxy)ethoxy)ethoxy)ethyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726)) represented by the following chemical formula 1-29 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0407] [Chemical formula 1-29]
[0408]
[0409] Example 1-30. Ligand Substitution Reaction 30 (LE-30)
[0410] The same method as in Example 1-1 was used except that 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-30 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0411] [Chemical formula 1-30]
[0412]
[0413] Example 1-31. Ligand Substitution Reaction 31 (LE-31)
[0414] The same procedure as in Example 1-1 was performed except that 2-(vinyloxy)ethyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-31 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 520 nm.
[0415] [Chemical formula 1-31]
[0416]
[0417] Example 1-32. Ligand Substitution Reaction 32 (LE-32)
[0418] The same procedure as in Example 1-1 was performed except that 2-(2-(vinyloxy)ethoxy)ethyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726)) represented by the following chemical formula 1-32 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0419] [Chemical formula 1-32]
[0420]
[0421] Example 1-33. Ligand Substitution Reaction 33 (LE-33)
[0422] The same method as in Example 1-1 was used except that 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-33 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0423] [Chemical formula 1-33]
[0424]
[0425] Example 1-34. Ligand Substitution Reaction 34 (LE-34)
[0426] The same method as in Example 1-1 was used except that 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-34 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0427] [Chemical formula 1-34]
[0428]
[0429] Example 1-35. Ligand Substitution Reaction 35 (LE-35)
[0430] The same method as in Example 1-1 was used except that 3-mercapto-N-(3,6,9,12-tetraoxapentadec-14-enyl)propanamide (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-35 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0431] [Chemical formula 1-35]
[0432]
[0433] Example 1-36. Ligand Substitution Reaction 36 (LE-36)
[0434] The same method as in Example 1-1 was used except that 3-mercapto-N-(3,6,9,12,15-pentaoxaoctadec-17-enyl)propanamide (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-36 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0435] [Chemical formula 1-36]
[0436]
[0437] Example 1-37. Ligand Substitution Reaction 37 (LE-37)
[0438] The same procedure as in Example 1-1 was performed except that 3-(3-(3-(allyloxy)propoxy)propoxy)propyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726)) represented by the following chemical formula 1-37 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0439] [Chemical formula 1-37]
[0440]
[0441] Example 1-38. Ligand Substitution Reaction 38 (LE-38)
[0442] The same method as in Example 1-1 was used except that 4,8,12,16-tetraoxanonadec-18-enyl 3-mercaptopropanoate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726) represented by the following chemical formula 1-38 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0443] [Chemical formula 1-38]
[0444]
[0445] Example 1-39. Ligand Substitution Reaction 39 (LE-39)
[0446] The same procedure as in Example 1-1 was performed except that 2-(2-(allyloxy)ethoxy)ethyl 3-aminopropanoate (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-39 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 520 nm.
[0447] [Chemical formula 1-39]
[0448]
[0449] Example 1-40. Ligand Substitution Reaction 40 (LE-40)
[0450] The same procedure as in Example 1-1 was performed except that 2-(2-(vinyloxy)ethoxy)ethyl 3-aminopropanoate (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-40 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 520 nm.
[0451] [Chemical formula 1-40]
[0452]
[0453] Example 1-41. Ligand Substitution Reaction 41 (LE-41)
[0454] The same procedure as in Example 1-1 was performed except that 2-aminoacetic acid-3,6,9,12,15-pentaoxaoctadec-17-enyl 2-aminoacetate (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-41 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0455] [Chemical formula 1-41]
[0456]
[0457] Example 1-42. Ligand Substitution Reaction 42 (LE-42)
[0458] The same procedure as in Example 1-1 was performed except that 2-aminoacetic acid-3,6,9,12,15-pentaoxaheptadec-16-enyl ester (3,6,9,12,15-pentaoxaheptadec-16-enyl 2-aminoacetate (self-synthesized; Tetrahedron 76 (2020) 131127)) represented by the following chemical formula 1-42 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0459] [Chemical formula 1-42]
[0460]
[0461] Example 1-43. Ligand Substitution Reaction 43 (LE-43)
[0462] The same procedure as in Example 1-1 was performed except that 3-aminopropanoic acid-3,6,9,12,15-pentaoxaheptadec-16-enyl 3-aminopropanoate (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-43 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0463] [Chemical formula 1-43]
[0464]
[0465] Example 1-44. Ligand Substitution Reaction 44 (LE-44)
[0466] The same procedure as in Example 1-1 was performed except that 3,6,9,12,15-pentaoxaoctadec-17-enyl 3-aminopropanoate (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-44 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0467] [Chemical formula 1-44]
[0468]
[0469] Example 1-45. Ligand Substitution Reaction 45 (LE-45)
[0470] The same procedure as in Example 1-1 was performed except that 3-amino-N-(3,6,9,12,15-pentaoxaoctadec-17-enyl)propanamide (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-45 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0471] [Chemical formula 1-45]
[0472]
[0473] Example 1-46. Ligand Substitution Reaction 46 (LE-46)
[0474] The same procedure as in Example 1-1 was performed except that 4,8,12,16-tetraoxanonadec-18-enyl 3-aminopropanoate (self-synthesized; Tetrahedron 76 (2020) 131127) represented by the following chemical formula 1-46 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0475] [Chemical formula 1-46]
[0476]
[0477] Example 1-47. Ligand Substitution Reaction 47 (LE-47)
[0478] The same method as in Example 1-1 was used except that 3-mercaptopropanethioate (S-2-(2-methoxyethoxy)ethyl 3-mercaptopropanethioate (self-synthesized; Journal of Medicinal Chemistry (J. Med. Chem.) 2019, 62, 2, 699-726)) represented by the following chemical formula 1-47 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0479] [Chemical formula 1-47]
[0480]
[0481] Example 1-48. Ligand Substitution Reaction 48 (LE-48)
[0482] The same method as in Example 1-1 was used except that S-2,5,8,11-tetraoxatridecan-13-yl 3-mercaptopropanethioate (self-synthesized; Bulletin of the Chemical Society of Japan, 1982, vol. 55, #7, p. 2303-2304) represented by the following chemical formula 1-48 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 521 nm.
[0483] [Chemical formula 1-48]
[0484]
[0485] Example 1-49. Ligand Substitution Reaction 49 (LE-49)
[0486] The same method as in Example 1-1 was used except that 3-mercaptopropanethioate (S-2,5,8,11,14-pentaoxahexadecan-16-yl 3-mercaptopropanethioate (self-synthesized; Bulletin of the Chemical Society of Japan, 1982, vol. 55, #7, p. 2303-2304) represented by the following chemical formula 1-49 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0487] [Chemical formula 1-49]
[0488]
[0489] Example 1-50. Ligand Substitution Reaction 50 (LE-50)
[0490] The same method as in Example 1-1 was used except that 3-mercaptopropanethioate (S-5,8,11-trioxa-2-thiatridecan-13-yl 3-mercaptopropanethioate (self-synthesized; Bulletin of the Chemical Society of Japan, 1982, vol. 55, #7, p. 2303-2304) represented by the following chemical formula 1-50 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0491] [Chemical formula 1-50]
[0492]
[0493] Example 1-51. Ligand Substitution Reaction 51 (LE-51)
[0494] The same method as in Example 1-1 was used except that 3-mercaptopropanethioate (S-5,8,11,14-tetraoxa-2-thiahexadecan-16-yl 3-mercaptopropanethioate (self-synthesized; Bulletin of the Chemical Society of Japan, 1982, vol. 55, #7, p. 2303-2304) represented by the following chemical formula 1-51 was used instead of the ligand used in Example 1-1. The maximum emission wavelength was 522 nm.
[0495] [Chemical formula 1-51]
[0496]
[0497] Comparative Example 1-1: Preparation of InP / ZnSe / ZnS core-shell quantum dots (1P) without ligand exchange reaction
[0498] A quantum dot powder (1P) was obtained from the quantum dot solution of Synthesis Example 1 with oleic acid bound to the surface.
[0499] Comparative Example 1-2: Ligand Substitution Reaction 52 (LE-52)
[0500] The same procedure as in Example 1-1 was carried out except that 8-phenyloctanoic acid (8-Phenyloctanoic acid, Alfa Aesar) represented by the following Chemical Formula 2-1 was used instead of the ligand used in Example 1-1.
[0501] [Chemical formula 2-1]
[0502]
[0503] Comparative Example 1-3: Ligand Substitution Reaction 53 (LE-53)
[0504] The same procedure as in Example 1-1 was carried out except that 6-cyclohexyl-hexanoic acid (6-cyclohexyl-hexanoic acid, manufactured by BOC Ceince Co., Ltd.) represented by the following chemical formula 2-2 was used instead of the ligand used in Example 1-1.
[0505] [Chemical formula 2-2]
[0506]
[0507] Comparative Example 1-4: Ligand Substitution Reaction 54 (LE-54)
[0508] The same procedure as in Example 1-1 was carried out except that mPEG-AA (Creative PEGWorks, MW350) represented by the following Chemical Formula 2-3 was used instead of the ligand used in Example 1-1.
[0509] [Chemical formula 2-3]
[0510]
[0511] Comparative Example 1-5: Ligand Substitution Reaction 55 (LE-55)
[0512] The same procedure as in Example 1-1 was carried out except that adipic acid monomethyl ester (Sigma-Aldrich) represented by the following Chemical Formula 2-4 was used instead of the ligand used in Example 1-1.
[0513] [Chemical formula 2-4]
[0514]
[0515] Comparative Example 1-6: Ligand Substitution Reaction 56 (LE-56)
[0516] The same procedure as in Example 1-1 was carried out except that malonic acid monophenylester (Alfa Chemistry Co., Ltd.) represented by the following Chemical Formula 2-5 was used instead of the ligand used in Example 1-1.
[0517] [Chemical formula 2-5]
[0518]
[0519] Comparative Example 1-7: Ligand Substitution Reaction 57 (LE-57)
[0520] The same procedures as in Example 1-1 were carried out except that N-phenyl-succinamic acid (Combi-Blocks) represented by the following Chemical Formula 2-6 was used instead of the ligand used in Example 1-1.
[0521] [Chemical formula 2-6]
[0522]
[0523] Comparative Example 1-8: Ligand Substitution Reaction 58 (LE-58)
[0524] The same procedures as in Example 1-1 were carried out except that 3-(cyclohexylcarbamoyl)propanoic acid (Angene Chemical Co., Ltd.) represented by the following Chemical Formula 2-7 was used instead of the ligand used in Example 1-1.
[0525] [Chemical formula 2-7]
[0526]
[0527] Examples 2-1 to 2-51 and Comparative Examples 2-1 to 2-8: Preparation of Quantum Dot Dispersion Liquid
[0528] Quantum dot dispersions were prepared according to the components and contents shown in Tables 1 to 4 below.
[0529] [Table 1]
[0530]
[0531] [Table 2]
[0532]
[0533] [Table 3]
[0534]
[0535] [Table 4]
[0536]
[0537] -LE-1 to LE-51: quantum dot powders of Examples 1-1 to 1-51
[0538] -P1: quantum dot powder of Comparative Example 1-1
[0539] -LE-52 to LE-58: Quantum dot powders of Comparative Examples 1-2 to 1-8
[0540] -M-1: 1,4-Butanediol diacrylate (BDDA)
[0541] -M-2: 1,6-Hexanediol diacrylate (HDDA)
[0542] -M-3: Pentaerithritol triacrylate (PETA)
[0543] -C-1: Propylene glycol monomethyl ether acetate
[0544] -C-2: n-Pentyl acetate
[0545] -C-3: Propylene glycol monomethyl ether
[0546] Examples 3-1 to 3-39 and Comparative Examples 3-1 to 3-6: Production of Photoconversion Curable Compounds
[0547] Photoconversion curable compositions were prepared according to the components and contents shown in Tables 5 to 7 below.
[0548] [Table 5]
[0549]
[0550] [Table 6]
[0551]
[0552] [Table 7]
[0553]
[0554] -A-1 to A-6: Quantum dot dispersions of Examples 2-1 to 2-6
[0555] -A-7 to A-8: Quantum dot dispersions of Examples 2-11 to 2-12
[0556] -A-9 to A-13: Quantum dot dispersions of Examples 2-14 to 2-18
[0557] -A-14: Quantum dot dispersion of Example 2-20
[0558] -A-15 to A-39: Quantum dot dispersions of Examples 2-27 to 2-51
[0559] -a-1 to a-2: Quantum dot dispersions of Comparative Examples 2-1 to 2-2
[0560] -a-3 to a-6: Quantum dot dispersions of Comparative Examples 2-4 to 2-8
[0561] -MN-1: ATM-4E (manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0562] -MN-2: Pentaerythritol triacrylate
[0563] -PI-1: Irgacure OXE-01 (manufactured by BASF)
[0564] - Scattering particles: TiO2 (manufactured by Huntsman, TR-88, particle size 220nm)
[0565] Experimental example
[0566] (1) Oxidative stability
[0567] The quantum efficiency (QY%) of the quantum dot powders of Examples 1-1 to 1-51 and Comparative Examples 1-1 to 1-8 at the initial stage of production and the absolute quantum efficiency (QY%) after being left at room temperature for 15 days were measured using QE-2100 (Otsuka Corporation).
[0568] Since the quantum efficiency decreases due to surface oxidation of quantum dots, the oxidation stability can be confirmed by measuring the decrease in quantum efficiency. That is, the oxidation stability can be confirmed by measuring ΔQY%. The above measurement results are shown in Table 8 below.
[0569] (2)Lightfastness
[0570] The quantum efficiency of the quantum dot powders of Examples 1-1 to 1-51 and Comparative Examples 1-1 to 1-8 at the initial stage of production and the absolute quantum efficiency after being placed in a blue LED light source at room temperature for 7 days were measured using QE-2100 (Otsuka Corporation).
[0571] If the surface of the quantum dot is oxidized due to a defect that is not protected by the ligand, the quantum efficiency decreases. The reliability can be confirmed by measuring the decrease in absolute quantum efficiency. The above measurement results are shown in Table 8 below.
[0572] [Table 8]
[0573]
[0574]
[0575] As shown in the results of Table 8, it can be confirmed that the quantum dots of Examples 1-1 to 1-51 of the present invention, which contain the ligand represented by Chemical Formula 1 on the surface, are prevented from being oxidized on the surface of the quantum dots, thereby suppressing the decrease in quantum efficiency. On the other hand, it can be confirmed that the quantum efficiency of the quantum dots of Comparative Examples 1-1 to 1-8 is greatly reduced.
[0576] Specifically, the quantum dots of Examples 1 to 1-51 maintain a quantum efficiency of more than 90% compared to the initial quantum efficiency even after being placed at room temperature for 15 days, and maintain a quantum efficiency of more than 80% compared to the initial quantum efficiency even after being placed in a blue LED light source at room temperature for 7 days, indicating excellent oxidation stability and light resistance.
[0577] On the other hand, it was confirmed that the quantum efficiency and light resistance of the quantum dots of Comparative Examples 1-1 to 1-8 were reduced. In particular, the quantum efficiency of the quantum dots of Comparative Examples 1-1 to 1-8 significantly decreased to less than about 50% compared to the initial quantum efficiency after being left at room temperature for 15 days.
[0578] As described above, it was confirmed that when the compound represented by Chemical Formula 1 is included as a ligand on the surface of the quantum dot, the surface of the quantum dot is protected and thus has excellent oxidation stability, and a decrease in quantum efficiency is prevented, thereby improving reliability.
[0579] (3) Viscosity stability evaluation
[0580] For the quantum dot dispersions of Examples 2-1 to 2-51 and Comparative Examples 2-1 to 2-8, an R-type viscosity tester (VISCOMETER MODEL RE120L SYSTEM, manufactured by Toki Sangyo Co., Ltd.) was used to measure the initial viscosity and the viscosity after storage at a low temperature of 5°C for 1 month at a rotation speed of 20 rpm and a temperature of 30°C. The viscosity stability was evaluated based on the viscosity change rate calculated in this way and according to the following evaluation criteria, and the results are shown in Table 9 below.
[0581] <Viscosity Stability Evaluation Criteria>
[0582] ○: Viscosity change rate is less than 105%
[0583] △: Viscosity change rate is greater than 105% and less than 110%
[0584] ×: Viscosity change rate is greater than 110%
[0585] (4) Dispersion particle size evaluation
[0586] The dispersion particle sizes of the quantum dot dispersions of Examples 2-1 to 2-51 and Comparative Examples 2-1 to 2-8 were measured using ELSZ-2000ZS (manufactured by Otsuka Corporation). The results are shown in Table 9 below.
[0587] [Table 9]
[0588]
[0589]
[0590] As shown in the results of Table 9 above, it can be confirmed that the quantum dot dispersions of Examples 2-1 to 2-51 of the present application have excellent viscosity stability and dispersed particle size. On the other hand, it can be confirmed that the quantum dot dispersions of Comparative Examples 2-1 to 2-8 have reduced viscosity stability and poor dispersed particle size.
[0591] (5) Manufacturing of light conversion coatings and evaluation of light conversion efficiency
[0592] The photoconversion curable compositions of Examples 3-1 to 3-39 and Comparative Examples 3-1 to 3-6 were coated on a 5 cm × 5 cm glass substrate by inkjet method, and then a 1 kW high pressure mercury lamp containing all g, h, and i rays was used as an ultraviolet light source at 1000 mJ / cm 2 After irradiation, the coating was heated in a heating oven at 180° C. for 30 minutes to produce a light conversion coating. The light conversion coating produced above was placed on a blue light source (XLamp XR-E LED, Royal blue 450, Cree), and the light conversion efficiency was measured and calculated using a brightness meter (CAS140CT Spectrometer, Instrumentsystems) using the following mathematical formula 1, and the results are shown in the following Table 10. The higher the light conversion efficiency (%), the more excellent the brightness can be obtained.
[0593] [Mathematical formula 1]
[0594]
[0595] (6) Evaluation of the number of continuous injections
[0596] After the light conversion curable compositions of Examples 3-1 to 3-39 and Comparative Examples 3-1 to 3-6 were filled in the inkjet printing equipment of Unijet, the temperature of the nozzle was fixed at 40°C, and then the ink was sprayed for 1 minute and then left for 30 minutes as one time, and this operation was repeated until the nozzle of the nozzle head was clogged and could not spray, thereby evaluating the number of continuous spraying, and the results are shown in the following Table 10. As the number of continuous spraying increases, excellent characteristics can be obtained in the continuous process of inkjetting.
[0597] (7) Evaluation of coating hardness
[0598] The degree of curing of the light conversion coating produced above was measured at a high temperature of 150° C. using a hardness meter (HM500; manufactured by Fischer), and the coating film hardness was evaluated according to the following evaluation criteria. The results are shown in Table 10 below.
[0599] <Evaluation criteria for coating hardness>
[0600] ○: Surface hardness is 50 or more
[0601] △: Surface hardness is 30 or more and less than 50
[0602] ×: Surface hardness less than 30
[0603] [Table 10]
[0604]
[0605]
[0606] As shown in the results of Table 10 above, it can be confirmed that the photoconversion curable compositions of Examples 3-1 to 3-39 of the present application have excellent properties in the inkjet continuous process, and the photoconversion coatings produced thereby are excellent in photoconversion efficiency and hardness. On the other hand, it can be confirmed that the photoconversion curable compositions of Comparative Examples 3-1 to 3-6 are not suitable for the inkjet continuous process, and their photoconversion efficiency and hardness are also poor.
Claims
1. A quantum dot having a ligand layer on its surface, The ligand layer comprises a compound represented by the following Chemical Formula 1, Chemical formula 1 In the chemical formula 1, A is CH=CH2 or -CH2CH=CH2, R1 is -(OCH2CH2) m -or-(OCH2CH2CH2) l -, R2 is a linear or branched alkylene group having 1 to 30 carbon atoms, L1 is an oxygen atom, a sulfur atom or -NH-, L2 is direct binding, D is an oxygen atom, X is a thiol group, m and l are each independently an integer of 1-150.
2. The quantum dot according to claim 1, characterized in that The ligand layer includes one or more compounds selected from the group consisting of the compounds represented by the following chemical formulas 1-27 to 1-38, Chemical formula 1-27 Chemical formula 1-28 Chemical formula 1-29 Chemical formula 1-30 Chemical formula 1-31 Chemical formula 1-32 Chemical formula 1-33 Chemical formula 1-34 Chemical formula 1-35 Chemical formula 1-36 Chemical formula 1-37 Chemical formula 1-38 3. The quantum dot according to claim 1, characterized in that The ligand layer further includes one or more selected from the group consisting of oleic acid, lauric acid, 2-(2-methoxyethoxy)acetic acid, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and succinic acid mono-[2-(2-methoxy-ethoxy)-ethyl] ester.
4. The quantum dot according to claim 1, characterized in that The quantum dot has a core-shell structure including a core and a shell covering the core.
5. The quantum dot according to claim 4, characterized in that: The core includes one or more of InP, InZnP, InGaP, CdSe, CdS, CdTe, ZnS, ZnSe, ZnTe, CdSeTe, CdZnS, CdSeS, PbSe, PbS, PbTe, AgInZnS, AgInGaS, HgS, HgSe, HgTe, GaN, GaP, GaAs, InGaN, InAs and ZnO.
6. The quantum dot according to claim 4, characterized in that The shell includes one or more of ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, InP, InS, GaP, GaN, GaO, GaS, InZnP, InGaP, InGaN, InZnSCdSe, PbS, TiO, SrSe and HgSe.
7. The quantum dot according to claim 1, characterized in that The quantum dots include one or more selected from the group consisting of AgInGaS / GaS, InP / ZnS, InP / ZnSe, InP / GaP / ZnS, InP / ZnSe / ZnS, InP / ZnSeTe / ZnS and InP / MnSe / ZnS. 8 . A quantum dot dispersion comprising the quantum dots according to claim 1 , and one or more of a monomer and a solvent. 9 . A photoconversion curable composition comprising the quantum dot dispersion according to claim 8 . 10 . The photoconversion curable composition according to claim 9 , which is a photoconversion ink composition or a photoconversion resin composition. 11 . The light conversion curable composition according to claim 9 , further comprising one or more of scattering particles, an alkali-soluble resin, a photopolymerizable compound, a photopolymerization initiator, and a solvent.
12. A quantum dot light emitting diode, comprising the quantum dot according to any one of claims 1 to 7. 13 . A quantum dot film comprising the quantum dots according to claim 1 . 14 . A cured film formed using the photoconversion curable composition according to claim 10 . 15 . The cured film according to claim 14 , which is a color filter or a light conversion laminate substrate. 16 . An image display device comprising the cured film according to claim 14 .
Citation Information
Patent Citations
Luminescence complex, composition including the complex, hardened member of the composition, optical sheet, backlight unit, and display device
KR101628065B1
Quantum dot-containing composition, wavelength conversion member, backlight unit and liquid crystal display device
KR1020180002716A
Curable resin composition cured film and display device
CN108445714A
Quantum dot having organic ligand and application thereof
CN108624320A
Light conversion resin composition, light conversion stacked material and image display device
CN110275392A